Developing Easy Listening Audio (ELA) as an Alternative Medium for Enhancing the Eight Grade Students’ Listening Learning Outcomes - Lestari Tika Wahyu; Dian Fadhilawati; Nita Sutanti (JOSAR (Journal of Students Academic Research), 2023)
The present study has the intention to create, validate, evaluate the effectiveness, and gain responses toward the developed product of Easy listening audio for enhancing the eight grade students’ listening learning outcomes in Blitar It was achieved by adapting Sugiyono's frameworks of developing the product into seven phases which covered; 1) problems identification and, solution identification, 2) designing and developing the product,3) validating and revising the product, 4) conducting product trials,5) collecting feedback from teachers and students, 6) evaluating and revising the product, and 7) finalizing it for publication. The research reported that the Easy Listening Audio comprised audio listening materials describing people, things, and animals, and three guidebooks for teachers, students, and the public. The validation process confirmed that the developed product was highly valid, with material validators rating it at 95% and media validators at 89%. The effectiveness of the product was also evident from the t-test results, which showed a value of less than 0.005, indicating a significant improvement in learning outcomes. Additionally, users responded positively to the product, with 91.6% of students rating it as "Very good" and 78.5% of teachers rating it as "Good." Therefore, it is recommended that teachers consider using the developed Easy Listening Audio as an alternative medium, particularly for teaching listening descriptive text in junior high schools